Model of Development of Tax Accounting using Tax Computer Program - Zulia Hanum; Jasman Saripuddin; Rini Astuti (Proceedings of AICS - Social Sciences, 2017)
One of the purposes of preparing Tax reports is to provide information to certain parties that will be used to make comparisons, assess the ability of a company, as well as a guide for decision-making. In order to meet the above objectives, the financial statements must be comparable. These comparisons can be done in two ways, namely horizontal and vertical. Horizontal comparison is a comparison of the financial statements of a company tax with another company for the same period, in which the concept can be easily where in the preparation when using existing software. This study aims to develop the model of taxation accounting learning by using the computer program Tax as a teaching material on lecture materials in college. A specific target to be achieved in this study is to release teaching materials in the form of financial accounting books prepared with the program Computer Taxation. To achieve these objectives, this research uses descriptive analysis to identify problems that exist in study of financial accountancy at college in Medan. These problems include the lack of students understanding in using computer programs Tax that has long been issued, and not motivated to study the program due to lack of guidance in implementing the practices undertaken. To find the factors that become obstacles in understanding the use of the program. With the identification of these factors, furthermore can be compiled a teaching materials to motivate students desiring to enjoy the teaching materials and the goal of educating the children of the nation can be achieved